P–196 Bacterial influence on oocyte quality - the secret of a successful fertilization. (6th August 2021) - Schenk, M; Voroshilina, E; Boldyreva, M; Koranda, M; Reinschissler, N; Weiss, G
Abstract: Study question: Is there a difference in bacterial composition of follicular fluid between oocytes developing a good quality blastocyst and oocytes that fail fertilization? Summary answer: Follicular fluids of oocytes failing fertilization show a different bacterial profile compared to follicular fluids of oocytes that were successfully fertilized. What is known already: The presence of pathogens in the female reproductive tract has been intensively investigated. Lactobacillus species are mainly associated with a healthy genital tract and good prognosis for a successful pregnancy. Studies of the bacterial composition of follicular fluids have been mainly undertaken in women participating in reproductive medicine treatment because of the nature to obtain the specimen. In most studies follicular fluids have been pooled for analysis. Information on separately collected follicular fluids is still rare. We hypothesized that the composition of bacteria within follicular fluids is responsible for the success of the fertilization process. Study design, size, duration: The study was designed and conducted at the Kinderwunsch Institut Schenk GmbH (Dobl, Austria) together with DNA-Technology. Follicular fluids from 46 patients undergoing IVF (in vitro fertilization) and ICSI (intracytoplasmic sperm injection) treatment were included and analyzed. Participants/materials, setting, methods: Follicular fluids from 46 patients were collected separately. 2 follicular fluids from each patient were screened for common bacteria of the genital tract. One from an oocyte developing a good quality blastocyst and one displaying fertilization failures. Samples were analyzed for bacterial composition using the Femoflor16 (DNA-Technology). Main results and the role of chance: Quantitative analysis revealed a higher total bacteria mass in follicles from oocytes that failed fertilization. Furthermore, Lactobacillus were not present in those follicles compared to good blastocyst follicles. In addition, Chlamydia trachomatis was found mainly in follicular fluid of not fertilized oocytes together with Eubacterium, Gardnarella and Trichomonas species. Interestingly, a trend of elevated levels of Ureaplasma species in follicular fluids of oocytes developing good quality blastocysts was observed. Limitations, reasons for caution: Contamination of follicular fluids due to the procedure of oocyte pick up and follicular fluid retrieval cannot be completely excluded. Results should be confirmed with a higher sample size. Wider implications of the findings: We assume that different bacterial compositions in follicular fluids are responsible for the destiny of the oocyte. It is tempting to speculate that bacterial analysis of follicular fluids may be beneficial to select to best oocytes in future IVF/ICSI treatments. Trial registration number: Not applicable